Konseling Individu Berbasis REBT Dengan Teknik Self Talk Untuk Meningkatkan Kepercayaan Diri Remaja SMP - Nita Dwi Anggraeni; Isrida Yul Arifiana (Journal of Psychology and Social Sciences, 2026)
Adolescence is a critical developmental period characterized by biological, psychological, and social changes, in which self-confidence plays an important role in psychosocial adjustment. This case study explored low self-confidence in a 16-year-old female adolescent (IS) who experienced bullying related to physical appearance and fear of negative social evaluation. A qualitative case study design was used with multimodal assessment, including interviews, observations, and psychological tests (FSCT, DAP, and Wartegg). Findings revealed low self-confidence, negative self-perception, social anxiety, and indecisiveness regarding future education. An individual counseling intervention using REBT combined with self-talk techniques showed positive initial changes in emotional regulation and self-confidence.